EXPERIMENTAL CHARACTERIZATION TECHNIQUES FOR TRANSITION METAL COMPLEX ANALYSIS - Syaima, Husna (JURNAL ATOMIK, 2024)
Due to their diverse properties and functionalities, metal complexes are central to various applications spanning chemistry, materials science, and beyond. The elucidation of metal complexes through rigorous analysis is paramount for understanding their structure, properties, and potential applications. This review article provides an overview of the techniques employed for analyzing metal complexes and highlights the importance of instrumental techniques utilized. Techniques such as X-ray crystallography, thermogravimetric analysis (TGA) and differential thermal analysis (DTA), Fourier-transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), and X-ray diffraction (XRD) are discussed in detail, showcasing their roles in probing different aspects of metal complex chemistry. By employing these analytical techniques, researchers can gain valuable insights into metal complexes' composition, structure, thermal stability, and electronic properties, driving innovation and progress in various scientific and technological fields. Continuous advancements in analytical techniques further enhance capabilities in metal complex analysis, paving the way for ground-breaking discoveries and transformative advancements in chemistry and related disciplines.